A Roadmap for Extreme-Mechanics Hydrogels: From Toughening Mechanisms to Intelligent System Integration - Tong, Aixin; Huang, Zhiyu; He, Annan; Qiao, Sijie; Shi, Zhicheng; Wang, Xiaotian; Chen, Zhen; Hu, Peiying; Wang, Kai; Qian, Jin; Xu, Weilin; Chen, Fengxiang (Nano-Micro Letters, 2026)
Hydrogels, as water-rich, three-dimensional polymer networks, have emerged as essential materials across diverse fields including bio-integrated electronics, load-bearing biomedical implants, and soft robotics. However, conventional hydrogels often fail under mechanical extremes, limiting their deployment in mechanically demanding environments. This review bridges this gap by presenting a transformative design paradigm that shifts the focus from merely robust hydrogels to intelligently adaptive systems capable of withstanding and dynamically responding to extreme mechanical environments. We first deconstruct the fundamental toughening mechanisms—including sacrificial bonding, topological entanglements, and nanocomposite reinforcement—that form the foundation of mechanical robustness. Moving beyond static strength, we critically examine how stimuli-responsive elements (e.g., temperature, light, pH, magnetic fields) can be integrated to enable real-time, dynamic modulation of mechanical properties. Advanced fabrication strategies, particularly bioinspired structuring and 3D printing, are highlighted as essential tools for achieving hierarchical architectures that optimize stress distribution and functional integration. Finally, we showcase pioneering applications in artificial muscles, wearable sensors, and adaptive tissue scaffolds, culminating in a forward-looking perspective on the convergence of artificial intelligence, multiscale modeling, and self-growing materials to guide the development of next-generation autonomous hydrogel systems. Highlights: 1 Scenario-adaptive design principles for extreme-mechanics hydrogels, connecting application-specific mechanical requirements with multiscale material and structural design. 2 Mechanistic integration of extreme mechanical performance and multi-environmental responsiveness, enabled by dynamic networks, nanocomposite hybridization, and biomimetic hardsoft architectures. 3 System-level perspective on hydrogels as active components in intelligent systems, emphasizing multiscale structuring and closed-loop “sense–think–act” functionality.